2000
DOI: 10.1002/1096-9098(200007)74:3<219::aid-jso13>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Solitary necrotic nodule of the liver misinterpreted as malignant lesion: Considerations on two cases

Abstract: In our experience, we document 2 cases of a rare and non-tumoral lesion of the liver misinterpreted as necrotic tumor: necrotic solitary nodule. In the first clinical case, ultrasound (US) showed a polylobated lesion (35 × 35 × 38 mm) at segment 8. Color-doppler identified a compression of celiac axis (Dunbar syndrome). Arteriography revealed a subtotal stenosis of celiac tripod soon after the emergence of the left gastric artery. FNAB-CT showed a highly cellulated tissue with a necrotic core surrounded by a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…De Luca et al 44 reported cases of necrotic nodules misdiagnosed as tumors with ultrasound. They emphasized that there was no correlation between US findings and histology.…”
Section: Discussionmentioning
confidence: 99%
“…De Luca et al 44 reported cases of necrotic nodules misdiagnosed as tumors with ultrasound. They emphasized that there was no correlation between US findings and histology.…”
Section: Discussionmentioning
confidence: 99%
“…PAS, Grocott and acid-fast staining all showed no bacterial, fungal, and parasitic infections [1][2][3][4]. In current study, the cases both had the typical image of SNN, PAS, and acid-fast staining was also negative.…”
Section: Discussionmentioning
confidence: 79%
“…The majority of patients were single nodule, and the minority were nodules. Average diameter was about 2 ∼ 3 cm; Serum CA-19, CEA and other tumor marker test results were normal [2][3][4]. In our cohorts of patients, one was in the left lobe of the liver parenchyma, the other one was in the right lobe under the liver capsule, and the nodule diameter was 1.8 cm and 4.0 cm, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations